Holmium laser enucleation of the prostate using Moses 2.0 vs non‐Moses: a randomised controlled trial. (1st November 2020) - Nevo, Amihay; Faraj, Kassem S.; Cheney, Scott M.; Moore, Jonathan P.; Stern, Karen L.; Borofsky, Michael; Gnessin, Ehud; Humphreys, Mitchell R.
Abstract : Objectives: To compare the enucleation efficiency of Moses 2.0 with non‐Moses technology in patients undergoing holmium laser enucleation of the prostate (HoLEP). Patients and Methods: A double‐blinded, randomised study of patients undergoing HoLEP at the Mayo Clinic in Arizona, using the Lumenis Pulse™ 120H laser system. Patients were randomised to either right lobe enucleation using Moses 2.0 and left lobe enucleation using non‐Moses, or the opposite. The primary outcome was individual lobe enucleation efficiency. Secondary outcomes included individual lobe laser time, laser energy, individual enucleation and haemostasis laser energies, and fibre burn back. Two independent reviewers watched videos of the procedures and provided a subjective evaluation of the technologies. Results: A total of 27 patients were included in the study. For the entire cohort, Moses 2.0 had less fibre degradation (3.5 vs 16.8 mm, P  < 0.01) compared to non‐Moses. When HoLEP procedures were performed by an expert, Moses 2.0 resulted in shorter enucleation time (21 vs 36.7 min, P  = 0.016) and higher enucleation efficiency (1.75 vs 1.05 g/min, P  = 0.05) compared to non‐Moses. When HoLEP was performed by trainees, the Moses 2.0 cohort had a shorter haemostasis laser time (4.1 vs 9 min, P  = 0.035) compared to the non‐Moses. Fibre degradation was lower with Moses 2.0 compared to non‐Moses for both experts and trainees. Moses 2.0 received a higher score than the standard technology for the incision sharpness, fibre control, tissue separation, tissue damage, haemostasis, visibility, and charring. The overall inter‐observer correlation coefficient was 0.63. Conclusion: Moses 2.0 has higher enucleation efficiency compared to non‐Moses when used by experts. The subjective evaluation favoured Moses 2.0.